Improving the process characteristics of cutting fibrous composite materials - Sychov, Yrij; Bryniuk, Oleksandr; Varodov, Kyrylo; Grechaniuk, Yaroslav (Eastern-European Journal of Enterprise Technologies, 2025)
This study explores the process of cutting fibrous polymer composite materials. The main reason for limiting the use of polymer composites is the deterioration of their performance properties after mechanical processing because of destruction of the surface layer. It is high time substantiated recommendations for the mechanical processing of fibrous polymer composites (FPCs) are provided. This could reduce the depth of destruction of an FPC surface layer to 20–50 μm and expand the area of functional application of these materials. An experimental study on the influence of cutting modes and geometric parameters of the cutting part of the tools on the technological components of the cutting force has been conducted, which made it possible to establish that the greatest influence on the cutting force when processing fibrous composites is exerted by the values of the geometric characteristics of the tool. Reducing the energy consumption for cutting to the level of 1.5 kN∙m/s helps minimize the influence of mechanical, thermal, and chemical factors on the destruction of the composite. FPCs have high elastic properties, which determines the features in the cutting process. As this leads to increased values of cutting forces on the rear surface, it is recommended to carry out processing by a sharpened tool at large values of the front γ and rear α angles of the blade. Determining the cutting force makes it possible to correctly assign the geometric parameters of the tool and estimate the processing error. The specified machining modes make it possible to reduce the depth of the defective layer by 10 times (RZ ≤ 20 mm, KB ≤ 5%, N ≤ 1012 spin/gr, M ≤ 50 μm) and increase the stability of the cutting tool by two times. The results could make it possible to improve the process of shaping articles from polymeric materials during production